Chaihu Shugan San and Zuogui Yin synergistically improve premature ovarian failure in a rat model via the PI3K/Akt/mTOR pathway - Fei Zhang; RuiFang Liu; ZhenLing Xu; WenJie Chen; XiYa Lu; Yang Wang (Translational Oncology)
Background: premature ovarian failure (POF) is a significant condition characterized by the early loss of ovarian function, often leading to infertility and other health complications. Traditional Chinese Medicine (TCM) formulations, such as Chaihu Shugan San and Zuogui Yin, have been used to address various gynecological disorders. This study aims to evaluate the therapeutic effects of Chaihu Shugan San, Zuogui Yin, and their combination on POI in a rat model and to elucidate the underlying mechanisms involving the PI3K/Akt/mTOR signaling pathway. Methods: In this study, a premature ovarian failure (POF) rat model was established using chronic unpredictable mild stress (CUMS) combined with cyclophosphamide injections. Rats were treated with Chaihu Shugan San, Zuogui Yin, or their combination. Key outcomes, including ovarian granulosa cell proliferation, follicular integrity, and hormonal levels (FSH and E2), were assessed. Histopathological changes in ovarian tissue were evaluated using hematoxylin and eosin (H&E) staining, while apoptosis was detected through immunohistochemistry and Western blot analysis of proteins such as Bcl-2, Bax, Caspase3, and Caspase9. The activity of the PI3K/Akt/mTOR signaling pathway was quantified using Western blot, and statistical significance was determined (P < 0.05). Results: The results showed that all three treatments significantly improved ovarian function in the POF rat model. Compared to the model group, Chaihu Shugan San, Zuogui Yin, and their combination increased granulosa cell proliferation (P < 0.01), reduced follicular atresia (P < 0.05), and normalized hormone levels (FSH: reduced by 36.5 %; E2: increased by 42.8 %, P < 0.05). Histopathological analysis confirmed preserved follicular structure and reduced apoptosis in treated groups. Western blot results revealed enhanced PI3K/Akt/mTOR pathway activity, with upregulated Bcl-2 expression (P < 0.01), downregulated Bax expression (P < 0.01), and decreased Caspase3 and Caspase9 levels (P < 0.05). Additionally, CyclinD2 and P70S6 K expression were significantly increased in treated groups, suggesting enhanced cell cycle progression and protein synthesis. Conclusion: Chaihu Shugan San, Zuogui Yin, and their combination exhibit potential efficacy as treatments for POF in rats by enhancing granulosa cell proliferation, preserving follicular integrity, and inhibiting apoptosis. These therapeutic effects are mediated through the activation of the PI3K/Akt/mTOR signaling pathway and regulation of apoptosis-related proteins. This study highlights the importance of further exploring apoptosis-related pathways to understand the therapeutic mechanisms of these TCM formulations, providing a foundation for new clinical strategies to manage POF and related reproductive health issues.